ENERGY POVERTY AND ITS EXISTENCE IN INDIA: A CRITICAL ANALYSIS - Narzary, Gwmwthao; Sarma, Gunajit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Energy is the main key for economic, social and physical development. Without energy we cannot access to basic services like safe drinking water, lighting, cooking, health care and education etc. Energy poverty is defined in different way by different researchers. Most of researchers are stated energy poverty is the unable access to modern energy for basic needs such as lighting and cooking. However, there is no single universal accepted tool for energy poverty estimate. Present study tries to find out whether energy poverty exist or not in India with the help of researchers have studied about energy poverty by using different approaches.